Lateral window maxillary sinus lift surgery: case report - FARIAS,Illa Oliveira Bitencourt (2022)
ABSTRACT The loss in height of the alveolar bone crest after tooth extraction makes rehabilitation of the posterior maxilla challenging due to low bone density and atrophy, in addition to pneumatization of the maxillary sinus. Maxillary sinus lift surgery prior to implant placement makes implant-supported rehabilitation feasible. This study aimed to describe a case report of maxillary sinus surgery using the side window technique prior to rehabilitation with a prosthesis supported by dental implants, highlighting the importance of planning to minimize intraoperative complications. This is a clinical case report of a 59-year-old male patient who was assisted at a private higher education institution complaining of edentulous spaces and the desire for rehabilitation with implants. He underwent rehabilitation planning, including the surgical treatment of maxillary sinus lifting using the side window technique. Bone gain was confirmed using cone beam computed tomography six months after the surgical approach to the maxillary sinus. The planning of rehabilitation of the posterior maxilla and careful sinus lift surgery using the side window technique is a predictable therapeutic option for clinical cases with bone gain in height of the posterior region of the maxilla prior to the installation of dental implants. The clinical case presented demonstrated success in the gain of bone volume in the posterior region of the maxilla, without postoperative complications, and the patient was still satisfied with the proposed treatment, awaiting complete implant-supported rehabilitation.